How does the English day program affect students’ speaking skill? A Systematic Literature Review - Dwi Yanti, Khairunnisa; Maghfiroh, Ana; Asiyah, Siti (LPPM Press, 2024)
This research aims to (1) explore what obstacles students experience in learning English language skills, (2) find out how the English Day program works, (3) find out how the English Day program contributes to improving speaking skills and abilities, and (4) investigate the various research methods used by researchers in selected articles. A literature review was applied as a method in this study with 10 articles reviewed. The articles reviewed are limited to: (1) articles taken from the Google Scholar and open knowledge maps database; (2) open access articles; (3) the topic is related to English day program. The review process, starting with a focused search, continues with thorough analysis, evaluation, and synthesis of the information gathered to gain a comprehensive understanding of the research topic. The results of this research show that students had several problems while implementing the English Day Program, such as psychological and linguistic problems. Apart from that, researchers also found that the English Day Program was proven to improve students' speaking skills. Apart from that, there are several things that influence students, such as motivation, self-confidence, understanding of English, interest, and mastery of vocabulary.